Drivers of particle sinking velocities in the Peruvian upwelling system - M. Baumann; A. J. Paul; J. Taucher; L. T. Bach; S. Goldenberg; P. Stange; F. Minutolo; U. Riebesell (Biogeosciences, 2023)
As one of Earth's most productive marine ecosystems, the Peruvian upwelling system transports large amounts of biogenic matter from the surface to the deep ocean. Whilst particle sinking velocity is a key factor controlling the biological pump, thereby affecting carbon sequestration and O2-depletion, it has not yet been measured in this system. During a 50 d mesocosm experiment in the surface waters off the coast of Peru, we assessed particle sinking velocities and their biogeochemical and physical drivers. We further characterized the general properties of exported particles under different phytoplankton communities and nutritional states. Average sinking velocities varied between size classes and ranged from 12.8 ± 0.7 m d−1 (particles 40–100 µm) to 19.4 ± 0.7 m d−1 (particles 100–250 µm) and 34.2 ± 1.5 m d−1 (particles 250–1000 µm) (± 95 % CI). Despite a distinct plankton succession from diatoms to dinoflagellates with concomitant 5-fold drop in opal ballasting, substantial changes in sinking velocity were not observed. This illustrates the complexity of counteracting factors driving the settling behaviour of marine particles. In contrast, we found higher sinking velocities with increasing particle size and roundness and decreasing porosity. Size had by far the strongest influence among these physical particle properties, despite a high amount of unexplained variability. Our study provides a detailed analysis of the drivers of particle sinking velocity in the Peruvian upwelling system, which allows modellers to optimize local particle flux parameterization. This will help to better project oxygen concentrations and carbon sequestration in a region that is subject to substantial climate-driven changes.